การหาภาวะเหมาะที่สุดในการะบวนการผลิตยางรีเคลมสำหรับขยะยางที่ประกอบด้วยยางธรรมชาติและยางอีพีดีเอ็ม - ภัสรา สุวรรณสิงห์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This research aims to study the optimum conditions for preparing reclaimed rubber from two types of rubber waste, consisting of natural rubber as the major component and EPDM rubber. Thermogravimetric analysis showed the proportion of rubber in rubber waste containing natural rubber as the major component and EPDM rubber was 53.5% and 56.0%, respectively. Preparation of reclaimed rubber from rubber waste by using a twin-screw extruder and varying the screw rotation speed at 150, 200 and 250 rpm, with each rotation speed using the mixing zone temperature at 200, 225 and 250 °C for the rubber waste containing natural rubber as a major component, while for EPDM waste, the mixing zone temperature was varied at 250, 275 and 300 °C and the rotation speed of the screw was the same as the first case. When testing Mooney viscosity, it found that the increasing of screw rotation speed and mixing zone temperature resulted in the decreasing of Mooney viscosity of reclaimed rubber. The reclaimed rubber was molded according to ISO/TS 16095:2021 and tested for mechanical properties. It found that the reclaimed rubber from rubber waste containing natural rubber as a major component prepared at screw rotation speed at 250 rpm and mixing zone temperature at 200 °C and EPDM waste prepared at screw rotation speed at 150 rpm and the mixing zone temperature at 275 °C showed the highest tensile strength and elongation at break. Because of the two types of reclaimed rubber obtained from the above conditions had a highest devulcanization percentage, resulting in the highest thermoplastic behavior. The reclaimed rubber was revulcanized, it gives the highest mechanical properties. The above conditions were used to study the influence of type and quantity of Tetrabenzylthiuram disulfide and Tetraisobutylthiuram disulfide as reclaiming agent. The addition of tetraisobutylthiuram disulfide at 1 and 3 part per hundred rubber for rubber waste containing natural rubber as the major component and EPDM waste, respectively is the best condition to prepare reclaimed rubber. Revulcanizate from both types of reclaimed rubber have the highest tensile strength and elongation at break. Due to, reclaimed rubber had highest percentage of devulcanization. When using both types of reclaimed rubber to replace virgin rubber according to the specific formula, it was found that when increase the amount of reclaimed rubber resulted in decreased the mechanical properties but, improved aging resistance of the vulcanized rubber.